A randomised, multi-centre, prospective, double blind pilot-study to evaluate safety and efficacy of the non-absorbable Optilene® Mesh Elastic versus the partly absorbable Ultrapro® Mesh for incisional hernia repair - Seiler, Christoph; Baumann, Petra; Kienle, Peter; Kuthe, Andreas; Kuhlgatz, Jens; Engemann, Rainer; Frankenberg, Moritz von; Knaebel, Hanns-Peter (BMC surgery, 2010)
Randomised controlled trials with a long term follow-up (3 to 10 years) have demonstrated that mesh repair is superior to suture closure of incisional hernia with lower recurrence rates (5 to 20% versus 20 to 63%). Yet, the ideal size and material of the mesh are not defined. So far, there are few prospective studies that evaluate the influence of the mesh texture on patient's satisfaction, recurrence and complication rate. The aim of this study is to evaluate, if a non-absorbable mesh (Optilene® Mesh Elastic) will result in better health outcomes compared to a partly absorbable mesh (Ultrapro® Mesh).
Gesehen am 21.06.2023